A Combination of Atorvastatin and Aspirin Enhances the Pro-Regenerative Interactions of Marrow Stromal Cells and Stroke-Derived Monocytes In Vitro - Satani, Nikunj; Zhang, Xu; Giridhar, Kaavya; Wewior, Natalia; Cai, Chunyan; Aronowski, Jaroslaw; Savitz, Sean I. (Frontiers in Pharmacology, 2021)
Background and purpose: Marrow stromal cells (MSCs) are being tested in clinical trials for stroke patients. MSCs appear to promote recovery through secretomes that promote modulation of immune cells, including myeloid phagocytes. Many stroke patients have comorbidities such as metabolic syndrome, hypertension, hypercholesterolemia, and diabetes for which they are prescribed medications that might affect the function of MSCs and monocytes (Mo) when they are administered in stroke patients. We studied the effects of the two most commonly prescribed stroke medications, statin and statin plus aspirin, on the secretomes of MSCs and their modulation of Mo derived from stroke patients. Methods: Human MSCs, Mo and their co-cultures were exposed to atorvastatin or atorvastatin plus aspirin followed by secretome analysis at 24h. Monocytes were isolated from healthy controls as well as stroke patients with NIHSS ranging from 11 to 20. Secretome composition was measured using multiplex immunoassay. We used MTT assay to measure proliferation of monocytes. The mixed model was used to analyze experimental data. P-values less than 0.05 were considered significant. Results: Atorvastatin and aspirin combination increased the release of IL-1RA from stroke Mo. In MSCs, atorvastatin and aspirin combination reduced the release of pro-inflammatory cytokines such as IL-6, IL-8, MCP-1 and IFN-γ. Atorvastatin alone reduced the release of IL-6, IL-8 and MCP-1 from co-cultures of stroke monocytes and MSCs. Combination of atorvastatin and aspirin had additive effect on reducing the secretion of IL-6 from co-cultures of stroke Mo and MSCs. Conclusions: Atorvastatin, alone and in combination with aspirin can promote anti-inflammatory effect by modulating the secretome profile of Mo and MSCs. Our results suggest that stroke trials involving the use of intravenous MSCs should consider the effect of aspirin and atorvastatin, both of which are administered to the majority of hospitalized ischemic stroke patients.